Phase transformation and grain growth in spray deposited wurtzite CuInS2 films - Pradeepkumar M.S.; Basu J.; Ahmad M.I. (My University, 2025)
We report the processing of large-grained chalcopyrite-CuIn(S,Se)2 (ch-CISSe) films using spray deposition of wurtzite-CuInS2 (wz-CIS) nanoparticle ink and subsequent selenization. Wurtzite to chalcopyrite phase transformation and grain growth were studied at varying selenization temperatures of 350, 400, 450, 500 and 550 °C for 15 min. On annealing in selenium (Se) atmosphere at 400 °C, the film transformed from wurtzite to chalcopyrite phase completely, while the grain growth took place at higher temperatures (500–550 °C), requiring greater amounts of Se substitution (Se/Se + S > 0.7). Differential scanning calorimetry (DSC) indicates that the phase transformation temperature is sensitive to the heating rate and has a second-order character. © 2022 Elsevier Ltd and Techna Group S.r.l.